Partisipasi Sosial Masyarakat Pada Program Kota Sehat Di Kota Bima - Ahmad Usman; Abdul Kadir; Firdaus Firdaus (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
Every government wants its citizens to be prosperous, healthy and happy. The UN Sustainable Development Goals (SDGs) is a global action plan agreed by world leaders, including Indonesia, to end poverty, reduce inequality and protect the environment. The healthy village program is a movement to create or realize a village with community conditions that have knowledge about health including nutrition, able to apply patterns or a culture of healthy living community social participation in the planning stage of the healthy village program in Bima City. The purpose of this research is to determine the level of community participation in social activities. Then this research method is descriptive quantitative research type, while the number of samples is 30 with a total population of 2,790. by developing an instrument in the form of a questionnaire given to each respondent. Then the data analysis technique used is to analyze the data based on the respondents' answers to the questioner. The results of the study are Based on the data obtained that efforts in preserving a healthy and clean village have been carried out by elements of the community, the efforts that have been made are in accordance with the interests of the activity.